Combined Effect of Calcium Nitrate and Fluorescent Pseudomonads on Bacterial Wilt Caused by Ralstonia Solanacearum - Lee, Kam Loong (2003)
A study on the combined effect of calcium nitrate and fluorescent Pseudomonads on bacterial wilt caused by Ralstonia solanacearum on tomato was carried out in the greenhouse and field. Greenhouse studies showed that application of calcium nitrate solution at 0.1 % and 0.5% on tomato seedlings prior to transplanting gave significant increase (p<0.01) on the fresh and dry weight of the treated seedlings compared to the 1% treatment and the non-treated control. Application of 0.5% calcium nitrate solution prior to transplanting, complemented with application of granular calcium nitrate after transplanting gave significant reduction (p<0.01) on bacterial wilt incidence on tomato seedlings planted in soil artificially infested with R. solanacearum at approximately 106 cfu/g oven-dry soil. Four strains of antagonistic Pseudomonads, that inhibited the growth of R. solanacearum on dual-culture plates, were tested individually in biopriming (approximately 1 X 108 cfu/ml in 1.5% methylcellulose) on their effects towards seed germination and biomass of the treated tomato seedlings. Pseudomonas putida strains KTS26 and AC1 individually gave significant (p<0.01) increase on germination (%) compared to when seeds were coated with methylcellulose only. Fresh weight of 30-days-old seedlings was significantly increased (p<0.01) by bio-priming with combination of KTS26 and AC1 , and with KTS26 alone. However, dry weight of seedlings was not affected by the treatments. G reenhouse studies were conducted to evaluate the combined effects of seed bio-priming with Pseudomonas pufida strains KTS26 and AC1 , either individually or in combination; application of calcium nitrate, at regular intervals, prior to and after transplanting; and application of Stonier's medium (half-strength) in controlling bacterial wilt on MT11 up to 6 weeks after transplanting. All combination of treatments significantly (p0.01) reduced the disease, compared to the non-treated control. However, no significant difference was observed between the treatments.